Penilaian Jurnal Akademik Evaluation of Academic Journals - Jyh Wee Sew (Kajian Malaysia, 2014)
The evaluation of academic journals is a scientific method that works towards a consistent academic achievement. A reliable evaluation method is important as it ensures that the data are trustworthy. This academic discussion examines the evaluation of academic journals from Australia. The method used in the report is examined and presented for the purview of academics. In reviewing the report critically, the validity of the journal titles selected is questionable thus this challenges the integrity of the report issued by the academic association concerned. Penilaian jurnal akademik merupakan satu langkah saintifik ke arah pemantapan prestasi akademik. Kaedah penilaian yang berkesahihan penting bagi mendapatkan data yang boleh dipercayai. Perbincangan ini meneliti satu penilaian prestasi jurnal akademik dari negara Australia. Kaedah yang digunakan dikaji dan dibentangkan untuk tatapan ahli akademik. Dalam imbasan kritis yang dilakukan, kesahihan judul jurnal yang dipilih menjadi tanda tanya justeru mencabar kewibawaan laporan yang dikeluarkan oleh persatuan pengajian ilmiah yang terbabit.